PENDAPATAN USAHATANI KUBIS DI KELURAHAN RURUKAN KECAMATAN TOMOHON TIMUR (Cabbage farming income in the Rurukan urban village, East Tomohon sub-district) - Ginansi Thomas; Melsje J. Memah; Martha M. Sendow (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2022)
This reasearch is aimed at knowing the income of the cabbage in Ward Rurukan of East Tomohon subdistrict, research was carried out in September to November 2021, with data used comes from primary and secondary data and is then descripted analyze.Research show that the average production of cabbage is in Ward Rurukan of East Tomohon subdistrict there are 5.556 Kg at a selling price of Rp.3000 per Kg with revenue cost of cabbae farmer per planting season as amount of Rp. 16.668.000 whereas production costs amount to Rp.3.853.956. the average cabbage farmers income per season in Ward Rurukan of East Tomohon subdistrict is amount Rp.12,814.044